Starup – Et jysk stednavn med historisk og arkæologisk potentiale - Nielsen, Michael Lerche (Kuml, 2014)
Starup – a Jutish place name with historical and archaeological potential Jutland’s six localities with the name of Starup or Stårup have not, with the exception of Sønder Starup on the edge of Haderslev Fjord, attracted any great archaeological interest. Most recently, the Starup area of the town of Løgumkloster has been dismissed as uninteresting in settlement-historical terms. This article attempts to rehabilitate this name group and presents the case for greater archaeological focus on these localities. It is argued that Starup was originally the term used for transit points between land and water traffic in the Viking Age and Early Middle Ages. In addition to the Starup localities, the article discusses a name complex with a possible, so far unknown, snekke name at Øster Starup. An alternative explanation is also given for Løgumkloster’s Latin name of Locus Dei. In conclusion, Starup is compared with other place names indicating trade and transit. It is argued that the Starup localities could have formed part of a more general transport infrastructure, just as the activities at this type of settlement can be perceived as a precursor to the urban developments of the Middle Ages. Michael Lerche Nielsen Afdeling for Navneforskning Nordisk Forskningsinstitut Københavns Universitet